The Development of A Bioassay Based on Heterologous Expression of M2 Ion-Channel Protein - Prasetyoputri, Anggia; Yuliaty, Neti; Tuharea, Warda; Febyanti, Alisin; Sunarko, Bambang; Atmosukarto, Ines I. C. (BRIN, 2010)
Emerging resistant viral strains combined with the limited availability of antivirals in a pandemic scenario highlight the need for the development of novel influenza antivirals. A bioassay based on the M2 protein of influenza virus - a potential target for antivirals - was developed to screen endophytic microbial extracts. M2 can be synthesized using PCR, thus eliminating the need for the handling of infectious specimen. Following cloning of the M2 gene into a pET backbone, the resultant plasmid was transformed into BL21 (DE3) pLyss E. coli cells. Cultures of these cells were set up at 37C following inoculation with a starter culture, to reach an OD at 600nm (OD600) of 0.4-0.6. Once at the required OD, the culture was split in two aliquots and expression of the M2 protein was induced in one of the duplicates with the addition of isopropyl β-D-thiogalactopyranoside (IPTG). Bacterial growth was monitored at 60-minute intervals. Exogenous expression of the M2 protein has been reported to decrease host cells viability, resulting in lower OD600 values. Our results suggest that the M2 protein was expressed and that overexpression of this protein resulted in consistently lower OD600 values of induced cultures compared with that of uninduced cultures. Based on this principle, extracts can be screened for their ability to block M2 function as identified by increased OD600 values.